Low-temperature forming method of bamboo powder / biodegradable high-barrier composite material

CN122898111APending Publication Date: 2026-10-13SHANGHAI BLOPAK NEW MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611195188.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

当成型温度降低后,聚乳酸熔融不充分、竹粉分散不均以及蒙脱土片层难以定向排列等问题更加明显,容易出现表面粗糙、厚度不均、局部团聚和层间结合不足;而过量增加增塑剂又可能降低材料的刚性、耐热性和阻隔性能

Benefits of technology

该竹粉/生物降解高阻隔复合材料的低温成型方法,通过对竹粉含水率及表面状态进行预先控制,将纳米纤维素预分散于热塑性淀粉塑化相中,并采用环氧大豆油对蒙脱土进行插层预处理,使竹粉、纳米纤维素和蒙脱土在进入树脂基体前分别形成适于低温混合的预分散状态;进一步通过聚乳酸与PBAT的分阶段软化、低温短时混炼、界面反应组分后段加入以及成型剪切方向控制,使复合物在降低整体热负荷的条件下仍能够获得稳定的流动性和界面结合状态,减少竹粉及热塑性淀粉的热降解、聚乳酸的水解断链以及挥发物引起的微孔缺陷,同时促使蒙脱土片层和纳米纤维素沿材料成型表面形成连续的片层—纤维复合阻隔结构,从而兼顾复合材料的低温成型性能、结构致密性、力学性能以及对氧气和水蒸气的阻隔性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898111A_ABST
    Figure CN122898111A_ABST
Patent Text Reader

Abstract

The application discloses a low-temperature forming method of bamboo powder / biodegradable high-barrier composite material, and relates to the technical field of biodegradable materials.The composite material comprises polylactic acid resin, PBAT resin, bamboo powder, thermoplastic starch, montmorillonite, nano-cellulose, vegetable wax, epoxy soybean oil, citric acid and auxiliary components.In the preparation process, the bamboo powder is graded, surface-activated and coated with vegetable wax, the nano-cellulose is pre-dispersed in the thermoplastic starch, and the montmorillonite is intercalated and pretreated with the epoxy soybean oil;then, the composite material is obtained through resin stage melting, pre-dispersed material adding, low-temperature short-time mixing, vacuum exhaust and directional forming.The application can reduce the thermal degradation of the bamboo powder and the starch, reduce the interface pores, promote the montmorillonite layers and the nano-cellulose to form a continuous layer-fiber composite barrier structure along the material forming surface, and improve the oxygen barrier property, the water vapor barrier property and the forming stability of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biodegradable materials technology, specifically a low-temperature molding method for bamboo powder / biodegradable high-barrier composite materials. Background Technology

[0002] With the development of green packaging materials, the preparation of biodegradable composite materials using bamboo powder, polylactic acid (PLA), PBAT, thermoplastic starch, and barrier fillers can improve biomass utilization while reducing the use of traditional petroleum-based plastics. Bamboo powder is characterized by its wide availability, renewability, and low cost; however, its surface contains many hydroxyl groups, resulting in high hygroscopicity, and its heat stability is lower than that of biodegradable resins such as PLA and PBAT. In existing composite material molding processes, high melting temperatures and long thermal residence times are typically required to ensure the full melting of PLA and the flow and dispersion of bamboo powder, starch, and inorganic barrier fillers within the resin matrix. Bamboo powder and thermoplastic starch are prone to dehydration, discoloration, or localized thermal degradation under high temperatures, releasing moisture and low-molecular-weight volatiles, which in turn form micropores, interfacial voids, and discontinuous regions within the molded material. Simultaneously, PLA is prone to molecular chain breakage in the presence of moisture and acidic substances, leading to a decrease in the strength, toughness, and barrier stability of the composite material. Therefore, although conventional high-temperature molding processes can improve resin flowability, they are prone to damaging bamboo powder, biodegradable resin, and interfacial bonding structures, making it difficult to balance molding quality and material properties.

[0003] On the other hand, bamboo powder / biodegradable high-barrier composite materials typically also contain barrier components such as montmorillonite and nanocellulose. Their barrier performance depends not only on the component content but also on the dispersion state of each barrier component in the resin, the orientation of the layers, and the density of the interface between the bamboo powder and the resin. Current technologies, when lowering the molding temperature, often only improve flowability by reducing the equipment set temperature or increasing the amount of plasticizer, lacking coordinated control over the pre-plasticization state of the raw materials, the resin melting sequence, the pre-dispersion state of the fillers, shear strength, and thermal residence time. When the molding temperature decreases, problems such as insufficient polylactic acid melting, uneven bamboo powder dispersion, and difficulty in the directional alignment of montmorillonite layers become more pronounced, easily leading to surface roughness, uneven thickness, local agglomeration, and insufficient interlayer bonding. Excessive addition of plasticizer may reduce the material's rigidity, heat resistance, and barrier performance. Therefore, current technologies still struggle to achieve sufficient resin plasticization, uniform bamboo powder coating, interface gap closure, and directional molding of the layered barrier structure at lower temperatures, and a significant contradiction remains between low-temperature processability and high barrier performance. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a low-temperature molding method for bamboo powder / biodegradable high-barrier composite materials, thereby solving the problems mentioned in the background section.

[0005] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a low-temperature molding method for a bamboo powder / biodegradable high-barrier composite material, which comprises the following formulation: polylactic acid resin, PBAT resin, bamboo powder, thermoplastic starch, montmorillonite, nanocellulose, plant wax, epoxidized soybean oil, citric acid, talc, stearic acid, and antioxidants. The low-temperature molding method for this composite material includes the following steps: S1. Raw material drying and particle size classification; S2, bamboo powder surface activation and plant wax coating treatment; Preparation of S3, thermoplastic starch and nanocellulose predispersants; S4. Preparation of montmorillonite intercalation predispersant; S5, staged melt mixing and interfacial reaction; S6, exhaust extrusion, granulation and barrier structure orientation molding.

[0006] To further optimize this technical solution, the composite material, by mass parts, includes the following components: 45-70 parts polylactic acid resin, 15-35 parts PBAT resin, 10-30 parts bamboo powder, 5-18 parts thermoplastic starch, 2-8 parts montmorillonite, 1-6 parts nanocellulose, 1-5 parts plant wax, 1-5 parts epoxidized soybean oil, 0.3-2 parts citric acid, 1-6 parts talc, 0.3-1.5 parts stearic acid, and 0.1-0.8 parts antioxidant.

[0007] Further optimization of this technical solution includes the following raw material drying and particle size classification treatment: Polylactic acid resin and PBAT resin were dried at 55–70°C for 4–8 hours to reduce their moisture content to no more than 0.2%. Montmorillonite and talc were dried at 80–100°C for 2–5 hours to reduce their moisture content to no more than 1%. Bamboo powder is sieved into coarse-grained bamboo powder of 80-120 mesh and fine-grained bamboo powder of 160-200 mesh, and mixed in a mass ratio of 2:1 to 4:1. Then it is dried at 80-100℃ until the moisture content is no more than 1.5% to obtain graded dried bamboo powder.

[0008] Further optimization of this technical solution includes the following: bamboo powder surface activation and plant wax coating treatment. Based on the graded and dried bamboo powder obtained in step S1, it is added to an alkaline aqueous solution with a mass concentration of 1% to 3%, and the mass ratio of bamboo powder to alkaline aqueous solution is 1:8 to 1:12. The mixture is stirred at 55 to 70°C for 30 to 60 minutes to remove some wax, ash and low molecular weight impurities from the surface of the bamboo powder. After processing, filter and wash with water until the washing liquid is neutral. Then, prepare a citric acid aqueous solution with a mass concentration of 0.5% to 2% using citric acid accounting for 30% to 60% of the total mass of citric acid in the formula. Immerse the washed bamboo powder in the solution for 20 to 40 minutes. The treated bamboo powder is dried at 80-100℃ until the moisture content is no more than 1.5%. Then, 40%-70% of the total mass of plant wax is heated to 75-90℃ to melt it and mixed with the dried bamboo powder for 5-15 minutes, so that the plant wax is attached to the surface of the bamboo powder in a discontinuous thin layer. After cooling and breaking it up, modified bamboo powder is obtained.

[0009] Further optimizing this technical solution, the preparation of the thermoplastic starch includes: Mix starch, glycerin and water in a mass ratio of 100:20-35:10-20, seal and let stand for 4-12 hours to allow the glycerin and water to evenly penetrate into the starch granules and form a mixture. The mixture is then added to a mixer or twin-screw extruder and plasticized at 110–140°C for 3–10 minutes. This process destroys the original crystalline structure of the starch granules and forms a continuous or semi-continuous plasticized phase. At the same time, free water is discharged through the exhaust port to obtain thermoplastic starch with a moisture content of no more than 3%.

[0010] Further optimization of this technical solution includes the preparation of the nanocellulose predispersant, comprising: Nanocellulose and thermoplastic starch are premixed at a temperature of 105–135°C for 2–8 minutes to coat and isolate nanocellulose with a diameter of 20–80 nanometers and a length of 0.5–3 micrometers, thus obtaining nanocellulose predispersed material.

[0011] Further optimization of this technical solution includes the preparation of the montmorillonite intercalation pre-dispersion material, comprising: Based on the obtained nanocellulose predispersed material, organomontmorillonite with an average particle size of 1-5 micrometers, an initial interlayer spacing of 1.8-3.0 nanometers and a moisture content of no more than 1% was premixed with epoxidized soybean oil, wherein the mass ratio of organomontmorillonite to epoxidized soybean oil used for premixing was 1:0.15-0.40. The two materials are stirred at 300-800 rpm for 10-30 minutes at 60-90℃ to allow the epoxidized soybean oil to penetrate into the gaps between the montmorillonite layers and reduce the bonding force between adjacent layers, thus obtaining the montmorillonite intercalation pre-dispersion material.

[0012] To further optimize this technical solution, the staged melt-blending process includes: Based on the obtained modified bamboo powder, nanocellulose predispersed material and montmorillonite intercalated predispersed material, the dried polylactic acid resin and PBAT resin were first added to the front section of a twin-screw extruder and melt-mixed at 150-165°C to disperse the PBAT resin in the continuous phase of polylactic acid resin. Subsequently, modified bamboo powder, nanocellulose predispersant and montmorillonite intercalated predispersant are added sequentially from the middle section of the extruder, and talc is added to disperse and shear the solid components in the resin matrix. After the components are initially dispersed, the remaining epoxidized soybean oil, citric acid and vegetable wax are added, along with stearic acid and antioxidants. The mixture is then further mixed at 160–175°C for 1–4 minutes to form a melt blend.

[0013] Further optimization of this technical solution includes the following steps: exhaust extrusion and granulation. Based on the melt blend formed in step S5, vacuum degassing is performed in the rear section of the twin-screw extruder, with the vacuum degree controlled at -0.06 to -0.095 MPa, to remove moisture, air and low-molecular-weight volatiles; The molten blend was then extruded through a die, cooled, and pelletized to obtain bamboo powder / biodegradable high-barrier composite material particles.

[0014] To further optimize this technical solution, the screw speed of the twin-screw extruder is 120-300 rpm, and the extrusion temperature is controlled sequentially from the feed end to the discharge end at 140-155℃, 150-165℃, 160-175℃, 165-175℃ and 155-170℃. After drying the obtained granules again at 55–70°C for 4–8 hours, they are formed by blown film, cast film, extrusion or hot pressing.

[0015] Compared with the prior art, the present invention provides a low-temperature molding method for bamboo powder / biodegradable high-barrier composite materials, which has the following beneficial effects: The low-temperature molding method for this bamboo powder / biodegradable high-barrier composite material involves pre-controlling the moisture content and surface state of the bamboo powder, pre-dispersing nanocellulose in the thermoplastic starch plasticized phase, and pre-treating montmorillonite with epoxidized soybean oil. This ensures that the bamboo powder, nanocellulose, and montmorillonite are in a pre-dispersed state suitable for low-temperature mixing before entering the resin matrix. Furthermore, through staged softening of polylactic acid and PBAT, low-temperature short-time mixing, late addition of interfacial reaction components, and control of molding shear direction, the composite material can still achieve stable flowability and interfacial bonding under reduced overall heat load. This reduces the thermal degradation of bamboo powder and thermoplastic starch, the hydrolytic chain scission of polylactic acid, and micropore defects caused by volatiles. At the same time, it promotes the formation of a continuous sheet-fiber composite barrier structure of montmorillonite sheets and nanocellulose along the molding surface of the material, thus taking into account the low-temperature molding performance, structural density, mechanical properties, and barrier performance against oxygen and water vapor of the composite material. Attached Figure Description

[0016] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0017] Figure 1 This is a schematic flowchart of a low-temperature molding method for a bamboo powder / biodegradable high-barrier composite material proposed in this invention. Detailed Implementation

[0018] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.

[0019] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0020] Secondly, the term "an embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places throughout this specification does not necessarily refer to the same embodiment, nor is it a single embodiment or an embodiment selectively excluded from other embodiments.

[0021] A bamboo powder / biodegradable high-barrier composite material, comprising the following components by mass parts: 45-70 parts polylactic acid resin, 15-35 parts PBAT resin, 10-30 parts bamboo powder, 5-18 parts thermoplastic starch, 2-8 parts montmorillonite, 1-6 parts nanocellulose, 1-5 parts plant wax, 1-5 parts epoxidized soybean oil, 0.3-2 parts citric acid, 1-6 parts talc, 0.3-1.5 parts stearic acid, and 0.1-0.8 parts antioxidant.

[0022] Polylactic acid resin is used as the main film-forming material; PBAT resin is used to improve the flexibility and impact resistance of the material; bamboo powder is used to increase the biomass content and reduce the material cost; thermoplastic starch is used to improve biodegradability; montmorillonite and nanocellulose together extend the penetration path of water vapor and oxygen inside the material to improve barrier properties; plant wax is used to reduce the water absorption of the material surface; epoxidized soybean oil is used to improve the compatibility between bamboo powder, thermoplastic starch and resin; citric acid is used to promote the bonding between the hydroxyl groups on the surface of thermoplastic starch and bamboo powder; talc is used to improve dimensional stability; stearic acid is used to improve processing fluidity; and antioxidants are used to reduce thermo-oxidative aging during melt processing.

[0023] The bamboo powder is composed of coarse-grained bamboo powder and fine-grained bamboo powder. The coarse-grained bamboo powder has a particle size of 80-120 mesh, and the fine-grained bamboo powder has a particle size of 160-200 mesh. The mass ratio of coarse-grained bamboo powder to fine-grained bamboo powder is 2:1 to 4:1. The moisture content of the bamboo powder before adding polylactic acid resin and PBAT resin is not higher than 1.5%. The coarse-grained bamboo powder is used to form a biomass support skeleton dispersed in the resin matrix, and the fine-grained bamboo powder fills the gaps between the coarse-grained bamboo powder, so that the bamboo powders of different particle sizes form a close-packed structure and reduce the formation of continuous pores inside the composite material.

[0024] Within the composite material, montmorillonite forms lamellar barrier units, and nanocellulose forms fibrous barrier units connecting adjacent lamellar barrier units. The average angle between the montmorillonite sheets and the molded surface of the composite material is no greater than 30°. The spacing between the montmorillonite sheets is 2.5–5.5 nanometers, allowing the montmorillonite sheets and nanocellulose to jointly form a lamellar-fiber composite barrier structure extending along the molded surface of the composite material, thereby restricting water and oxygen molecules from directly passing through the composite material in a direction perpendicular to the molded surface.

[0025] The plant wax is carnauba wax, which is divided into plant wax for bamboo powder coating and plant wax for melt mixing. The plant wax for bamboo powder coating accounts for 40% to 70% of the total mass of the plant wax. The plant wax for bamboo powder coating is melted at 75 to 90°C and mixed with bamboo powder that has undergone surface pretreatment for 5 to 15 minutes to distribute the plant wax on the surface of the bamboo powder. Then, the bamboo powder coated with plant wax is cooled and dispersed. The remaining plant wax is added after the polylactic acid resin and PBAT resin have completed preliminary melting. By placing the plant wax separately on the surface of the bamboo powder and in the continuous resin phase, the plant wax is prevented from being concentrated in the resin phase, thus avoiding the unsealed moisture absorption channels of the bamboo powder.

[0026] A portion of the citric acid is used for the surface pretreatment of bamboo powder, and the remainder is added together with thermoplastic starch. A portion of the epoxidized soybean oil is used for the predisposition of organomontmorillonite, and the remainder is added during the melt mixing of polylactic acid resin, PBAT resin, pretreated bamboo powder, and thermoplastic starch. The melt mixing temperature is 160–175°C, and the mixing time after the addition of epoxidized soybean oil and citric acid is 1–4 minutes. This allows the carboxyl groups of citric acid, the hydroxyl groups on the surface of bamboo powder and thermoplastic starch, and the epoxy groups of epoxidized soybean oil to form an interfacial bond structure under melt conditions, thereby reducing the interfacial gap between the bamboo powder phase, the thermoplastic starch phase, and the resin matrix.

[0027] See Figure 1 A method for preparing a bamboo powder / biodegradable high-barrier composite material includes the following steps: S1. Raw material drying and particle size classification. Weigh out the following raw materials according to the formula: polylactic acid resin, PBAT resin, bamboo powder, thermoplastic starch preparation materials, montmorillonite, nanocellulose, plant wax, epoxidized soybean oil, citric acid, talc, stearic acid, and antioxidant. Dry the polylactic acid resin and PBAT resin separately at 55–70℃ for 4–8 hours until their moisture content is no higher than 0.2%. Dry the montmorillonite and talc separately at 80–100℃ for 2–5 hours until their moisture content is no higher than 1%. Sieve the bamboo powder into coarse-grained bamboo powder (80–120 mesh) and fine-grained bamboo powder (160–200 mesh), and mix them at a mass ratio of 2:1 to 4:1. Then dry the mixture at 80–100℃ until the moisture content is no higher than 1.5%, obtaining graded and dried bamboo powder. By controlling the moisture content of resin, bamboo powder and inorganic fillers, the porosity caused by moisture vaporization during subsequent melt mixing is reduced. At the same time, the interstitial porosity inside the composite material is reduced by utilizing the interstitial filling effect between the two types of bamboo powder.

[0028] S2. Bamboo powder surface activation and plant wax coating treatment. Based on the graded and dried bamboo powder obtained in step S1, the bamboo powder is added to an alkaline aqueous solution with a mass concentration of 1% to 3%, and the mass ratio of bamboo powder to alkaline aqueous solution is 1:8 to 1:12. The mixture is stirred at 55 to 70°C for 30 to 60 minutes to remove some of the wax, ash, and low-molecular-weight impurities from the surface of the bamboo powder. After treatment, the mixture is filtered and washed with water until the washing liquid is neutral. Then, a citric acid aqueous solution with a mass concentration of 0.5% to 2% is prepared using citric acid accounting for 30% to 60% of the total mass of citric acid in the formula. The washed bamboo powder is then immersed in the solution for 20 to 40 minutes. The treated bamboo powder is dried at 80–100℃ until the moisture content is no higher than 1.5%. Then, 40%–70% of the total plant wax is heated to 75–90℃ to melt it, and mixed with the dried bamboo powder for 5–15 minutes, allowing the plant wax to adhere to the bamboo powder surface in a discontinuous thin layer. After cooling and dispersing, modified bamboo powder is obtained. The plant wax coating layer is used to seal some of the moisture absorption channels on the bamboo powder surface, but does not completely cover the active groups on the bamboo powder surface, thus balancing moisture resistance and interfacial bonding ability.

[0029] S3. Preparation of thermoplastic starch and nanocellulose predispersant. Following the bamboo powder interface pretreatment completed in step S2, starch, glycerol, and water are mixed at a mass ratio of 100:20–35:10–20, sealed, and allowed to stand for 4–12 hours to allow glycerol and water to uniformly penetrate the starch granules. The mixture is then added to a mixer or twin-screw extruder and plasticized at 110–140°C for 3–10 minutes. This disrupts the original crystalline structure of the starch granules, forming a continuous or semi-continuous plasticized phase. Simultaneously, free water is discharged through the exhaust port, yielding thermoplastic starch with a moisture content not exceeding 3%. Nanocellulose is then premixed with the thermoplastic starch at a mass ratio of 1:2–1:6 at a premixing temperature of 105–135°C for 2–8 minutes. This allows nanocellulose with a diameter of 20–80 nm and a length of 0.5–3 μm to be coated and isolated by the thermoplastic starch, resulting in a nanocellulose predispersant. By first dispersing nanocellulose in a hydrophilic thermoplastic starch plasticizing phase, fiber entanglement and local aggregation of nanocellulose after it directly enters the resin matrix are inhibited.

[0030] S4. Preparation of Montmorillonite Intercalation Predispersant. Based on the nanocellulose predispersant obtained in step S3, organic montmorillonite with an average particle size of 1–5 micrometers, an initial interlayer spacing of 1.8–3.0 nanometers, and a moisture content not exceeding 1% is premixed with a portion of the epoxidized soybean oil in the formulation. The mass ratio of organic montmorillonite to epoxidized soybean oil used for premixing is 1:0.15–0.40. The two are stirred at 300–800 rpm for 10–30 minutes at 60–90°C to allow the epoxidized soybean oil to penetrate into the interlayer gaps of montmorillonite and reduce the bonding force between adjacent layers, thus obtaining the montmorillonite intercalation predispersant. After predispersion, the interlayer spacing of montmorillonite increases to 2.5–5.5 nanometers to improve the ability of montmorillonite to form intercalation structures or partial exfoliation structures under subsequent melt shearing, and to prevent montmorillonite from being distributed in the form of large-sized stacked agglomerates within the composite material.

[0031] S5. Staged melt mixing and interfacial reaction. Based on the modified bamboo powder obtained in step S2, the nanocellulose predispersant obtained in step S3, and the montmorillonite intercalated predispersant obtained in step S4, the dried polylactic acid resin and PBAT resin are first added to the front section of a twin-screw extruder and melt-mixed at 150-165°C to disperse the PBAT resin in the continuous phase of the polylactic acid resin. Subsequently, the modified bamboo powder, nanocellulose predispersant, and montmorillonite intercalated predispersant are added sequentially from the middle section of the extruder, along with talc powder, to disperse and shear the solid components in the resin matrix. After the components are initially dispersed, the remaining epoxidized soybean oil, citric acid, and vegetable wax are added, along with stearic acid and antioxidants. The mixture is then further mixed at 160-175°C for 1-4 minutes, with the mass ratio of epoxidized soybean oil to citric acid controlled at 2:1-5:1. During the mixing process, the carboxyl groups of citric acid, the hydroxyl groups on the surface of bamboo powder and thermoplastic starch react with the epoxy groups of epoxidized soybean oil at the interface, forming a stable interfacial bond structure between the bamboo powder phase, the thermoplastic starch phase, and polylactic acid resin and PBAT resin; the remaining plant wax is dispersed near the interface of the resin continuous phase and the bamboo powder to reduce the possibility of water penetration along the interfacial gaps.

[0032] S6. Exhaust extrusion, granulation, and barrier structure orientation molding. Based on the melt blend formed in step S5, vacuum exhaust is performed in the rear section of a twin-screw extruder, with the vacuum level controlled at -0.06 to -0.095 MPa, to remove moisture, air, and low-molecular-weight volatiles. Subsequently, the melt blend is extruded through a die, cooled, and pelletized to obtain bamboo powder / biodegradable high-barrier composite material particles. The screw speed of the twin-screw extruder is 120–300 rpm, and the extrusion temperature is controlled sequentially from the feed end to the discharge end at 140–155℃, 150–165℃, 160–175℃, 165–175℃, and 155–170℃. After drying the obtained particles again at 55–70°C for 4–8 hours, they are shaped by blown film, cast film, extrusion, or hot pressing. During the shaping process, a shearing action is applied along the material surface to ensure that the average angle between the montmorillonite sheets and the material shaping surface is no greater than 30°, and that the nanocellulose is distributed between adjacent montmorillonite sheets, thereby forming a sheet-fiber composite barrier structure extending along the shaping surface, prolonging the diffusion path of oxygen and water vapor inside the material, and obtaining a bamboo powder / biodegradable high barrier composite material.

[0033] In the following examples and comparative examples, the polylactic acid resin used was extrusion-grade polylactic acid resin, the PBAT resin used was extrusion-grade PBAT resin, the bamboo powder used was moso bamboo powder, the thermoplastic starch was prepared from corn starch, glycerin, and water, the montmorillonite used was organomontmorillonite, the nanocellulose used was cellulose nanofibers, the plant wax used was carnauba wax, the alkaline aqueous solution used was sodium hydroxide aqueous solution, and the antioxidants used were antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1. The composite material particles were formed into sheets using a casting molding method.

[0034] Example 1: A bamboo powder / biodegradable high-barrier composite material, by weight parts, comprises 45 parts polylactic acid resin, 15 parts PBAT resin, 10 parts bamboo powder, 5 parts thermoplastic starch, 2 parts organomontmorillonite, 1 part cellulose nanofiber, 1 part carnauba wax, 1 part epoxidized soybean oil, 0.3 parts citric acid, 1 part talc, 0.3 parts stearic acid, 0.05 parts antioxidant 1010, and 0.05 parts antioxidant 168.

[0035] S1. Raw material drying and particle size classification. Weigh each raw material according to the above formula. Dry polylactic acid resin and PBAT resin separately at 62.5℃ for 6 hours, so that the moisture content of both polylactic acid resin and PBAT resin is not higher than 0.2%; dry organomontmorillonite and talc powder separately at 90℃ for 3.5 hours, so that the moisture content of both organomontmorillonite and talc powder is not higher than 1%. Sieve the bamboo powder into 100-mesh coarse-particle bamboo powder and 180-mesh fine-particle bamboo powder, with a mass ratio of coarse-particle bamboo powder to fine-particle bamboo powder of 3:1; mix the two types of bamboo powder and dry them at 90℃, so that the moisture content of the bamboo powder is not higher than 1.5%, to obtain graded and dried bamboo powder.

[0036] S2. Surface activation of bamboo powder and coating with carnauba wax. The graded and dried bamboo powder obtained in step S1 is added to a 2% sodium hydroxide aqueous solution (mass ratio of bamboo powder to sodium hydroxide aqueous solution is 1:10), and stirred at 62.5℃ for 45 minutes. After treatment, the mixture is filtered and washed with deionized water until the pH of the washing solution is 7. 0.135 parts of citric acid are used to prepare a 1.25% citric acid aqueous solution, and the washed bamboo powder is added to the citric acid aqueous solution for 30 minutes. The treated bamboo powder is dried at 90℃ until the moisture content is no higher than 1.5%. 0.55 parts of carnauba wax are heated to 82.5℃ and kept molten. The dried bamboo powder is added to the molten carnauba wax and mixed for 10 minutes. After cooling to room temperature, the mixture is dispersed to obtain modified bamboo powder. The remaining 0.45 parts of carnauba wax are reserved for addition in step S5.

[0037] S3. Preparation of thermoplastic starch and cellulose nanofiber predispersant. Weigh out 5 parts of corn starch, glycerol, and water according to a mass ratio of 100:27.5:15 for preparing thermoplastic starch. Mix the three components thoroughly, seal and let stand for 8 hours, then add to a twin-screw extruder and plasticize at 125°C for 6.5 minutes. Remove free water through the exhaust port to obtain thermoplastic starch with a moisture content not exceeding 3%. The cellulose nanofibers have an average diameter of 50 nm and an average length of 1.75 μm. Take 1 part of cellulose nanofiber and thermoplastic starch at a mass ratio of 1:4, premix at 120°C for 5 minutes to obtain the cellulose nanofiber predispersant; the remaining thermoplastic starch will be added in step S5.

[0038] S4. Preparation of organo-montmorillonite intercalation predispersant. The organo-montmorillonite has an average particle size of 3 micrometers, an initial interlayer spacing of 2.4 nanometers, and a moisture content of no more than 1%. Two parts of organo-montmorillonite are mixed with 0.55 parts of epoxidized soybean oil and stirred at 550 rpm for 20 minutes at 75°C to obtain the organo-montmorillonite intercalation predispersant. After predispersion, the interlayer spacing of the organo-montmorillonite is 4.0 nanometers. The remaining 0.45 parts of epoxidized soybean oil are reserved for addition in step S5.

[0039] S5. Staged melt mixing and interfacial reaction. 45 parts of dried polylactic acid resin and 15 parts of PBAT resin were added to the front section of a twin-screw extruder and melt-mixed at 157.5°C. Subsequently, the modified bamboo powder obtained in step S2, the cellulose nanofiber pre-dispersion obtained in step S3, the remaining thermoplastic starch, the organomontmorillonite intercalated pre-dispersion obtained in step S4, and 1 part of talc were added sequentially from the middle section of the twin-screw extruder. After preliminary mixing of all components, the remaining 0.45 parts of epoxidized soybean oil, the remaining 0.165 parts of citric acid, the remaining 0.45 parts of carnauba wax, 0.3 parts of stearic acid, 0.05 parts of antioxidant 1010, and 0.05 parts of antioxidant 168 were added, and mixing continued at 167.5°C for 2.5 minutes. The total mass ratio of epoxidized soybean oil to citric acid was 3.33:1.

[0040] S6. Extrusion, Granulation, and Casting. The molten blend formed in step S5 is fed to the rear section of a twin-screw extruder for vacuum degassing, with a vacuum level of -0.0775 MPa. The twin-screw extruder operates at a screw speed of 210 rpm, and the five temperature zones from the feed end to the discharge end are set at 147.5℃, 157.5℃, 167.5℃, 170℃, and 162.5℃, respectively. The molten blend is extruded through a die, cooled, and pelletized to obtain bamboo powder / biodegradable high-barrier composite material granules. The obtained granules are dried at 62.5℃ for 6 hours, and then cast using a casting machine with a casting roller temperature of 40℃ and a traction speed of 8 m / min to obtain composite material sheets with a thickness of 0.10 mm. The average angle between the organomontmorillonite layers in the composite material and the sheet forming surface is no greater than 30°, and the average spacing between the organomontmorillonite layers is 4.0 nm.

[0041] Example 2: A bamboo powder / biodegradable high-barrier composite material, by weight parts, comprises 57.5 parts polylactic acid resin, 25 parts PBAT resin, 20 parts bamboo powder, 11.5 parts thermoplastic starch, 5 parts organomontmorillonite, 3.5 parts cellulose nanofibers, 3 parts carnauba wax, 3 parts epoxidized soybean oil, 1.15 parts citric acid, 3.5 parts talc, 0.9 parts stearic acid, 0.225 parts antioxidant 1010, and 0.225 parts antioxidant 168.

[0042] S1. Raw material drying and particle size classification. Weigh each raw material according to the above formula. Dry polylactic acid resin and PBAT resin separately at 62.5℃ for 6 hours, so that the moisture content of both polylactic acid resin and PBAT resin is not higher than 0.2%; dry organomontmorillonite and talc powder separately at 90℃ for 3.5 hours, so that the moisture content of both organomontmorillonite and talc powder is not higher than 1%. Sieve the bamboo powder into 100-mesh coarse-particle bamboo powder and 180-mesh fine-particle bamboo powder, with a mass ratio of coarse-particle bamboo powder to fine-particle bamboo powder of 3:1; mix the two types of bamboo powder and dry them at 90℃, so that the moisture content of the bamboo powder is not higher than 1.5%, to obtain graded and dried bamboo powder.

[0043] S2. Bamboo powder surface activation and carnauba wax coating treatment. The graded and dried bamboo powder obtained in step S1 was added to a 2% sodium hydroxide aqueous solution (mass ratio of bamboo powder to sodium hydroxide aqueous solution: 1:10), and stirred at 62.5℃ for 45 minutes. After treatment, the mixture was filtered and washed with deionized water until the pH of the washing solution reached 7. 0.5175 parts of citric acid were used to prepare a 1.25% citric acid aqueous solution, and the washed bamboo powder was added to the citric acid aqueous solution for 30 minutes. The treated bamboo powder was dried at 90℃ until the moisture content did not exceed 1.5%. 1.65 parts of carnauba wax were heated to 82.5℃ and kept molten. The dried bamboo powder was added to the molten carnauba wax and mixed for 10 minutes. After cooling to room temperature, the mixture was dispersed to obtain modified bamboo powder. The remaining 1.35 parts of carnauba wax were reserved for addition in step S5.

[0044] S3. Preparation of thermoplastic starch and cellulose nanofiber predispersant. Corn starch, glycerol, and water were weighed according to a mass ratio of 100:27.5:15 to prepare 11.5 parts of thermoplastic starch. The three components were mixed evenly, sealed, and allowed to stand for 8 hours. Then, the mixture was added to a twin-screw extruder and plasticized at 125°C for 6.5 minutes. Free water was discharged through the exhaust port to obtain thermoplastic starch with a moisture content not exceeding 3%. The cellulose nanofibers had an average diameter of 50 nm and an average length of 1.75 μm. 3.5 parts of cellulose nanofibers were mixed with thermoplastic starch at a mass ratio of 1:4 and pre-mixed at 120°C for 5 minutes to obtain the cellulose nanofiber predispersant. The remaining thermoplastic starch was reserved for addition in step S5.

[0045] S4. Preparation of organo-montmorillonite intercalation predispersant. The organo-montmorillonite has an average particle size of 3 micrometers, an initial interlayer spacing of 2.4 nanometers, and a moisture content of no more than 1%. Five parts of organo-montmorillonite are mixed with 1.375 parts of epoxidized soybean oil and stirred at 550 rpm for 20 minutes at 75°C to obtain the organo-montmorillonite intercalation predispersant. After predispersion, the interlayer spacing of the organo-montmorillonite is 4.0 nanometers. The remaining 1.625 parts of epoxidized soybean oil are reserved for addition in step S5.

[0046] S5. Staged melt mixing and interfacial reaction. 57.5 parts of dried polylactic acid resin and 25 parts of PBAT resin were added to the front section of a twin-screw extruder and melt-mixed at 157.5°C. Subsequently, the modified bamboo powder obtained in step S2, the cellulose nanofiber pre-dispersion obtained in step S3, the remaining thermoplastic starch, the organomontmorillonite intercalated pre-dispersion obtained in step S4, and 3.5 parts of talc were added sequentially from the middle section of the twin-screw extruder. After preliminary mixing of all components, the remaining 1.625 parts of epoxidized soybean oil, the remaining 0.6325 parts of citric acid, the remaining 1.35 parts of carnauba wax, 0.9 parts of stearic acid, 0.225 parts of antioxidant 1010, and 0.225 parts of antioxidant 168 were added, and the mixture was further mixed at 167.5°C for 2.5 minutes. The total mass ratio of epoxidized soybean oil to citric acid was 2.61:1.

[0047] S6. Extrusion, Granulation, and Casting. The molten blend formed in step S5 is fed to the rear section of a twin-screw extruder for vacuum degassing, with a vacuum level of -0.0775 MPa. The twin-screw extruder operates at a screw speed of 210 rpm, and the five temperature zones from the feed end to the discharge end are set at 147.5℃, 157.5℃, 167.5℃, 170℃, and 162.5℃, respectively. The molten blend is extruded through a die, cooled, and pelletized to obtain bamboo powder / biodegradable high-barrier composite material granules. The obtained granules are dried at 62.5℃ for 6 hours, and then cast using a casting machine with a casting roller temperature of 40℃ and a traction speed of 8 m / min to obtain composite material sheets with a thickness of 0.10 mm. The average angle between the organomontmorillonite layers in the composite material and the sheet forming surface is no greater than 30°, and the average spacing between the organomontmorillonite layers is 4.0 nm.

[0048] This embodiment uses the same bamboo powder particle size distribution, raw material drying conditions, bamboo powder surface treatment method, nanocellulose pre-dispersion method, montmorillonite intercalation pretreatment method, and low-temperature staged melt mixing conditions as in Example 1. Each raw material is added according to the mass proportions specified in this embodiment. After mixing, vacuum degassing, extrusion granulation, and low-temperature molding are performed to obtain composite material test samples.

[0049] Example 3: A bamboo powder / biodegradable high-barrier composite material, by weight parts, comprises 70 parts polylactic acid resin, 35 parts PBAT resin, 30 parts bamboo powder, 18 parts thermoplastic starch, 8 parts organomontmorillonite, 6 parts cellulose nanofibers, 5 parts carnauba wax, 5 parts epoxidized soybean oil, 2 parts citric acid, 6 parts talc, 1.5 parts stearic acid, 0.4 parts antioxidant 1010, and 0.4 parts antioxidant 168.

[0050] S1. Raw material drying and particle size classification. Weigh each raw material according to the above formula. Dry polylactic acid resin and PBAT resin separately at 62.5℃ for 6 hours, so that the moisture content of both polylactic acid resin and PBAT resin is not higher than 0.2%; dry organomontmorillonite and talc powder separately at 90℃ for 3.5 hours, so that the moisture content of both organomontmorillonite and talc powder is not higher than 1%. Sieve the bamboo powder into 100-mesh coarse-particle bamboo powder and 180-mesh fine-particle bamboo powder, with a mass ratio of coarse-particle bamboo powder to fine-particle bamboo powder of 3:1; mix the two types of bamboo powder and dry them at 90℃, so that the moisture content of the bamboo powder is not higher than 1.5%, to obtain graded and dried bamboo powder.

[0051] S2. Bamboo powder surface activation and carnauba wax coating treatment. The graded and dried bamboo powder obtained in step S1 was added to a 2% sodium hydroxide aqueous solution (mass ratio of bamboo powder to sodium hydroxide aqueous solution: 1:10), and stirred at 62.5℃ for 45 minutes. After treatment, the mixture was filtered and washed with deionized water until the pH of the washing solution reached 7. 0.9 parts of citric acid were used to prepare a 1.25% citric acid aqueous solution, and the washed bamboo powder was added to the citric acid aqueous solution for 30 minutes. The treated bamboo powder was dried at 90℃ until the moisture content did not exceed 1.5%. 2.75 parts of carnauba wax were heated to 82.5℃ and kept molten. The dried bamboo powder was added to the molten carnauba wax and mixed for 10 minutes. After cooling to room temperature, the mixture was dispersed to obtain modified bamboo powder. The remaining 2.25 parts of carnauba wax were reserved for addition in step S5.

[0052] S3. Preparation of thermoplastic starch and cellulose nanofiber predispersant. Corn starch, glycerol, and water were weighed according to a mass ratio of 100:27.5:15 to prepare 18 parts of thermoplastic starch. After mixing the three components evenly, the mixture was sealed and allowed to stand for 8 hours. Then, it was added to a twin-screw extruder and plasticized at 125°C for 6.5 minutes. Free water was discharged through the exhaust port to obtain thermoplastic starch with a moisture content not exceeding 3%. The cellulose nanofibers had an average diameter of 50 nm and an average length of 1.75 μm. Six parts of cellulose nanofibers were mixed with thermoplastic starch at a mass ratio of 1:4 and pre-mixed at 120°C for 5 minutes to obtain the cellulose nanofiber predispersant. The remaining thermoplastic starch was reserved for addition in step S5.

[0053] S4. Preparation of organo-montmorillonite intercalation predispersant. The organo-montmorillonite has an average particle size of 3 micrometers, an initial interlayer spacing of 2.4 nanometers, and a moisture content of no more than 1%. Eight parts of organo-montmorillonite are mixed with 2.2 parts of epoxidized soybean oil and stirred at 550 rpm for 20 minutes at 75°C to obtain the organo-montmorillonite intercalation predispersant. After predispersion, the interlayer spacing of the organo-montmorillonite is 4.0 nanometers. The remaining 2.8 parts of epoxidized soybean oil are reserved for addition in step S5.

[0054] S5. Staged melt mixing and interfacial reaction. 70 parts of dried polylactic acid resin and 35 parts of PBAT resin were added to the front section of a twin-screw extruder and melt-mixed at 157.5°C. Subsequently, the modified bamboo powder obtained in step S2, the cellulose nanofiber pre-dispersion obtained in step S3, the remaining thermoplastic starch, the organomontmorillonite intercalated pre-dispersion obtained in step S4, and 6 parts of talc were added sequentially from the middle section of the twin-screw extruder. After preliminary mixing of all components, the remaining 2.8 parts of epoxidized soybean oil, the remaining 1.1 parts of citric acid, the remaining 2.25 parts of carnauba wax, 1.5 parts of stearic acid, 0.4 parts of antioxidant 1010, and 0.4 parts of antioxidant 168 were added, and the mixture was further mixed at 167.5°C for 2.5 minutes. The total mass ratio of epoxidized soybean oil to citric acid was 2.5:1.

[0055] S6. Extrusion, Granulation, and Casting. The molten blend formed in step S5 is fed to the rear section of a twin-screw extruder for vacuum degassing, with a vacuum level of -0.0775 MPa. The twin-screw extruder operates at a screw speed of 210 rpm, and the five temperature zones from the feed end to the discharge end are set at 147.5℃, 157.5℃, 167.5℃, 170℃, and 162.5℃, respectively. The molten blend is extruded through a die, cooled, and pelletized to obtain bamboo powder / biodegradable high-barrier composite material granules. The obtained granules are dried at 62.5℃ for 6 hours, and then cast using a casting machine with a casting roller temperature of 40℃ and a traction speed of 8 m / min to obtain composite material sheets with a thickness of 0.10 mm. The average angle between the organomontmorillonite layers in the composite material and the sheet forming surface is no greater than 30°, and the average spacing between the organomontmorillonite layers is 4.0 nm.

[0056] This embodiment uses the same raw material pretreatment and low-temperature molding method as in Example 1. Considering the high amount of bamboo powder and inorganic barrier components added, the screw speed was adjusted to 220 rpm without increasing the maximum processing temperature, and the vacuum degree of the vacuum exhaust section was controlled to -0.085 MPa. Dispersion was achieved by improving the melt shearing action and the ability to remove volatiles, thus obtaining the composite material test sample.

[0057] Comparative Example 1: A bamboo powder / biodegradable composite material, by weight parts, comprises 66 parts polylactic acid resin, 25 parts PBAT resin, 20 parts bamboo powder, 11.5 parts thermoplastic starch, 3 parts carnauba wax, 3 parts epoxidized soybean oil, 1.15 parts citric acid, 3.5 parts talc, 0.9 parts stearic acid, 0.225 parts antioxidant 1010, and 0.225 parts antioxidant 168.

[0058] S1. Raw material drying and particle size classification. Weigh each raw material according to the above formula. Dry polylactic acid resin and PBAT resin separately at 62.5℃ for 6 hours, so that the moisture content of both polylactic acid resin and PBAT resin is not higher than 0.2%; dry talc powder at 90℃ for 3.5 hours, so that the moisture content of talc powder is not higher than 1%. Sieve bamboo powder into 100-mesh coarse-particle bamboo powder and 180-mesh fine-particle bamboo powder, with a mass ratio of coarse-particle bamboo powder to fine-particle bamboo powder of 3:1; mix the two types of bamboo powder and dry at 90℃, so that the moisture content of bamboo powder is not higher than 1.5%, to obtain graded and dried bamboo powder.

[0059] S2. Surface activation of bamboo powder and coating with carnauba wax. The graded and dried bamboo powder obtained in step S1 was added to a 2% sodium hydroxide aqueous solution (mass ratio of bamboo powder to sodium hydroxide aqueous solution: 1:10), and stirred at 62.5℃ for 45 minutes. After treatment, the mixture was filtered and washed with deionized water until the pH of the washing solution reached 7. 0.5175 parts of citric acid were used to prepare a 1.25% citric acid aqueous solution, and the washed bamboo powder was added to the citric acid aqueous solution for 30 minutes. The treated bamboo powder was dried at 90℃ until the moisture content did not exceed 1.5%. 1.65 parts of carnauba wax were heated to 82.5℃ and kept molten. The dried bamboo powder was added to the molten carnauba wax and mixed for 10 minutes. After cooling to room temperature, the mixture was dispersed to obtain modified bamboo powder. The remaining 1.35 parts of carnauba wax were reserved for addition in step S4.

[0060] S3. Preparation of thermoplastic starch. Weigh out the corn starch, glycerol, and water required to prepare 11.5 parts of thermoplastic starch according to a mass ratio of corn starch: 27.5:15. Mix the three components thoroughly, seal and let stand for 8 hours, then add to a twin-screw extruder and plasticize at 125℃ for 6.5 minutes. Remove free water through the exhaust port to obtain thermoplastic starch with a moisture content not exceeding 3%.

[0061] S4. Staged melt mixing. 66 parts of dried polylactic acid resin and 25 parts of PBAT resin were added to the front section of a twin-screw extruder and melt-mixed at 157.5°C. Subsequently, modified bamboo powder obtained in step S2, thermoplastic starch obtained in step S3, and 3.5 parts of talc powder were added sequentially from the middle section of the twin-screw extruder. After the initial mixing of all components, 3 parts of epoxidized soybean oil, the remaining 0.6325 parts of citric acid, the remaining 1.35 parts of carnauba wax, 0.9 parts of stearic acid, 0.225 parts of antioxidant 1010, and 0.225 parts of antioxidant 168 were added, and the mixture was further mixed at 167.5°C for 2.5 minutes.

[0062] S5. Extrusion, Granulation, and Casting. The molten blend formed in step S4 is fed to the rear section of a twin-screw extruder for vacuum degassing, with a vacuum level of -0.0775 MPa. The twin-screw extruder operates at a screw speed of 210 rpm, and the five temperature zones from the feed end to the discharge end are set at 147.5℃, 157.5℃, 167.5℃, 170℃, and 162.5℃, respectively. The molten blend is extruded through a die, cooled, and pelletized to obtain bamboo powder / biodegradable composite material granules. The resulting granules are dried at 62.5℃ for 6 hours, and then cast using a casting machine with a casting roller temperature of 40℃ and a traction speed of 8 m / min to produce composite material sheets with a thickness of 0.10 mm.

[0063] In this comparative example, 8.5 parts of polylactic acid resin were used to replace 5 parts of montmorillonite and 3.5 parts of nanocellulose in Example 2 to maintain the same total mass of the formulation. Except for not preparing nanocellulose predispersant and montmorillonite intercalation predispersant, the bamboo powder treatment, feeding sequence, melting temperature, screw speed, vacuum degassing, and molding conditions were the same as in Example 2.

[0064] Comparative Example 2: A bamboo powder / biodegradable composite material, by weight parts, comprises 64.65 parts polylactic acid resin, 25 parts PBAT resin, 20 parts bamboo powder, 11.5 parts thermoplastic starch, 5 parts organomontmorillonite, 3.5 parts cellulose nanofibers, 3.5 parts talc, 0.9 parts stearic acid, 0.225 parts antioxidant 1010, and 0.225 parts antioxidant 168.

[0065] S1. Raw material drying and particle size classification. Weigh each raw material according to the above formula. Dry polylactic acid resin and PBAT resin separately at 62.5℃ for 6 hours, so that the moisture content of both polylactic acid resin and PBAT resin is not higher than 0.2%; dry organomontmorillonite and talc powder separately at 90℃ for 3.5 hours, so that the moisture content of both organomontmorillonite and talc powder is not higher than 1%. Sieve the bamboo powder into 100-mesh coarse-particle bamboo powder and 180-mesh fine-particle bamboo powder, with a mass ratio of coarse-particle bamboo powder to fine-particle bamboo powder of 3:1; mix the two types of bamboo powder and dry them at 90℃, so that the moisture content of the bamboo powder is not higher than 1.5%, to obtain graded and dried bamboo powder.

[0066] S2. Alkali Treatment of Bamboo Powder. The graded and dried bamboo powder obtained in step S1 is added to a 2% (w / w) sodium hydroxide aqueous solution, with a mass ratio of bamboo powder to sodium hydroxide aqueous solution of 1:10. The mixture is stirred at 62.5℃ for 45 minutes. After treatment, the mixture is filtered and washed with deionized water until the pH of the washing solution is 7. The washed bamboo powder is then dried at 90℃ until the moisture content of the bamboo powder does not exceed 1.5%, yielding alkali-treated bamboo powder.

[0067] S3. Preparation of thermoplastic starch and cellulose nanofiber predispersant. Corn starch, glycerol, and water were weighed according to a mass ratio of 100:27.5:15 to prepare 11.5 parts of thermoplastic starch. After mixing the three components evenly, the mixture was sealed and allowed to stand for 8 hours. Then, it was added to a twin-screw extruder and plasticized at 125°C for 6.5 minutes. Free water was discharged through the exhaust port to obtain thermoplastic starch with a moisture content not exceeding 3%. The cellulose nanofibers had an average diameter of 50 nm and an average length of 1.75 μm. 3.5 parts of cellulose nanofibers were mixed with thermoplastic starch at a mass ratio of 1:4 and pre-mixed at 120°C for 5 minutes to obtain the cellulose nanofiber predispersant. The remaining thermoplastic starch was reserved for addition in step S4.

[0068] S4. Staged melt mixing. 64.65 parts of dried polylactic acid resin and 25 parts of PBAT resin were added to the front section of a twin-screw extruder and melt-mixed at 157.5°C. Subsequently, the alkali-treated bamboo powder obtained in step S2, the cellulose nanofiber pre-dispersion obtained in step S3, the remaining thermoplastic starch, 5 parts of untreated organic montmorillonite and 3.5 parts of talc were added sequentially from the middle section of the twin-screw extruder. After the initial mixing of all components, 0.9 parts of stearic acid, 0.225 parts of antioxidant 1010 and 0.225 parts of antioxidant 168 were added, and the mixture was further mixed at 167.5°C for 2.5 minutes.

[0069] S5. Extrusion, Granulation, and Casting. The molten blend formed in step S4 is fed to the rear section of a twin-screw extruder for vacuum degassing, with a vacuum level of -0.0775 MPa. The twin-screw extruder operates at a screw speed of 210 rpm, and the five temperature zones from the feed end to the discharge end are set at 147.5℃, 157.5℃, 167.5℃, 170℃, and 162.5℃, respectively. The molten blend is extruded through a die, cooled, and pelletized to obtain bamboo powder / biodegradable composite material granules. The resulting granules are dried at 62.5℃ for 6 hours, and then cast using a casting machine with a casting roller temperature of 40℃ and a traction speed of 8 m / min to produce composite material sheets with a thickness of 0.10 mm.

[0070] In this comparative example, 7.15 parts of polylactic acid resin were used to replace 3 parts of plant wax, 3 parts of epoxidized soybean oil, and 1.15 parts of citric acid in Example 2 to maintain a consistent total mass of the formulation. Bamboo powder was treated with only alkaline aqueous solution and dried, without citric acid treatment or plant wax coating; montmorillonite was not pre-intercalated with epoxidized soybean oil, and the remaining processing conditions were the same as in Example 2.

[0071] Comparative Example 3: A bamboo powder / biodegradable composite material, by weight parts, comprises 57.5 parts polylactic acid resin, 25 parts PBAT resin, 20 parts bamboo powder, 11.5 parts thermoplastic starch, 5 parts organomontmorillonite, 3.5 parts cellulose nanofibers, 3 parts carnauba wax, 3 parts epoxidized soybean oil, 1.15 parts citric acid, 3.5 parts talc, 0.9 parts stearic acid, 0.225 parts antioxidant 1010, and 0.225 parts antioxidant 168.

[0072] S1. Raw material drying and particle size classification. Weigh each raw material according to the above formula. Dry polylactic acid resin and PBAT resin separately at 62.5℃ for 6 hours, so that the moisture content of both polylactic acid resin and PBAT resin is not higher than 0.2%; dry organomontmorillonite and talc powder separately at 90℃ for 3.5 hours, so that the moisture content of both organomontmorillonite and talc powder is not higher than 1%. Sieve the bamboo powder into 100-mesh coarse-particle bamboo powder and 180-mesh fine-particle bamboo powder, with a mass ratio of coarse-particle bamboo powder to fine-particle bamboo powder of 3:1; mix the two types of bamboo powder and dry them at 90℃, so that the moisture content of the bamboo powder is not higher than 1.5%, to obtain graded and dried bamboo powder.

[0073] S2. Preparation of thermoplastic starch. Weigh out the corn starch, glycerol, and water required to prepare 11.5 parts of thermoplastic starch according to a mass ratio of corn starch, glycerol, and water of 100:27.5:15. Mix the three components thoroughly, seal and let stand for 8 hours, then add to a twin-screw extruder and plasticize at 125℃ for 6.5 minutes. Remove free water through the exhaust port to obtain thermoplastic starch with a moisture content not exceeding 3%.

[0074] S3. One-time high-temperature melt mixing. 57.5 parts polylactic acid resin, 25 parts PBAT resin, 20 parts graded dried bamboo powder, 11.5 parts thermoplastic starch, 5 parts organomontmorillonite, 3.5 parts cellulose nanofibers, 3 parts carnauba wax, 3 parts epoxidized soybean oil, 1.15 parts citric acid, 3.5 parts talc, 0.9 parts stearic acid, 0.225 parts antioxidant 1010, and 0.225 parts antioxidant 168 are added to a twin-screw extruder in one step. The organomontmorillonite was not pre-dispersed with epoxidized soybean oil, the cellulose nanofibers were not pre-mixed with thermoplastic starch, and the bamboo powder was not treated with citric acid or coated with carnauba wax. The twin-screw extruder is set to five temperature zones from the feed end to the discharge end at 165℃, 175℃, 185℃, 190℃, and 185℃, with a screw speed of 180 rpm, for one-time melt mixing of all components.

[0075] S4. Extrusion, Granulation, and Casting. The molten blend formed in step S3 is fed to the rear section of a twin-screw extruder for vacuum degassing at a vacuum level of -0.0775 MPa. The molten blend is extruded through a die, cooled, and pelletized to obtain bamboo powder / biodegradable composite material granules. The resulting granules are dried at 62.5°C for 6 hours, and then cast using a casting machine with a casting roller temperature of 40°C and a traction speed of 8 m / min to produce composite material sheets with a thickness of 0.10 mm.

[0076] The amounts of each component in this comparative example are the same as in Example 2, but the bamboo powder is not treated with citric acid and pre-coated with plant wax, the nanocellulose is not pre-mixed with thermoplastic starch, and the montmorillonite is not pre-mixed with epoxidized soybean oil. All components are added to a twin-screw extruder at once, with the temperature zones set sequentially to 165°C, 175°C, 185°C, 190°C, and 185°C, and the screw speed at 180 rpm. After melt mixing, vacuum degassing, extrusion granulation, and molding, the test sample of Comparative Example 3 is obtained.

[0077] The composite materials prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to the tests shown in Table 1 below to verify the actual performance of the composite materials. The samples prepared in each example and comparative example were conditioned in an environment with a temperature of 23±2℃ and a relative humidity of 50±5% for at least 48 hours. Oxygen permeability, water vapor permeability, and tensile properties were all tested using samples with a thickness of 0.10±0.01 mm; if there were differences in the measured thickness of different samples, the permeability should be converted to the same thickness before lateral comparison.

[0078] Table 1

[0079] The effectiveness of this invention can be evaluated from three aspects: material composition, interface structure, and molding process by conducting tests on the molding appearance, oxygen permeability, water vapor permeability, tensile strength, elongation at break, water absorption, melt mass flow rate, montmorillonite interlayer spacing, barrier unit orientation state, interfacial porosity, continuous low-temperature molding stability, and biodegradability of Examples 1-3 and Comparative Examples 1-3.

[0080] Example 1 uses the lower limits of each component, with a relatively high proportion of resin matrix and low amounts of bamboo powder, thermoplastic starch, and barrier fillers. It is expected to have good melt flowability and continuous molding stability, a relatively smooth material surface, and relatively stable tensile strength and elongation at break. However, due to the low amounts of montmorillonite, nanocellulose, and plant waxes, their effect on extending the oxygen and water vapor permeation pathways is relatively limited. Therefore, Example 1 is mainly used to verify that the formulation of this invention can still achieve stable low-temperature molding and maintain basic barrier properties and mechanical properties under conditions of low amounts of biomass and barrier components.

[0081] Example 2 uses intermediate amounts of each component, resulting in a relatively balanced ratio among polylactic acid resin, PBAT resin, bamboo powder, thermoplastic starch, montmorillonite, nanocellulose, and interface control components. Bamboo powder forms a biomass support structure, thermoplastic starch supports and disperses nanocellulose, montmorillonite sheets and nanocellulose together form a tortuous gas permeation path, and plant waxes, epoxidized soybean oil, and citric acid are used to reduce the hygroscopicity of bamboo powder and improve the interfacial bonding between bamboo powder, starch, and resin. Therefore, Example 2 is suitable as the main example, and its test results should primarily be used to illustrate that the material achieves a good overall balance between oxygen barrier properties, water vapor barrier properties, water absorption, interfacial porosity, tensile properties, and low-temperature molding stability.

[0082] Example 3 uses the upper limits of each component, with relatively high additions of bamboo powder, thermoplastic starch, montmorillonite, and nanocellulose. This can be used to verify the material properties under conditions of high biomass content and high barrier filler content. Theoretically, higher contents of montmorillonite and nanocellulose can further increase the diffusion paths of oxygen and water vapor, and higher contents of plant wax can enhance the moisture-proof effect of the bamboo powder surface and resin interface. However, increased solid component content can also increase melt viscosity and may increase the risk of filler agglomeration and interface defects. Therefore, the focus of the test in Example 3 is to confirm whether the material can still maintain a continuous molding state after pre-dispersion, staged feeding, improved shear strength, and vacuum degassing, and to avoid a significant decrease in tensile properties and surface quality due to high filler content.

[0083] Comparative Example 1 did not include montmorillonite or nanocellulose; only polylactic acid resin was used to supplement the corresponding mass. The main difference between this comparative example and Example 2 lies in the sheet-fiber composite barrier structure. If the oxygen permeability and water vapor permeability of Example 2 are lower than those of Comparative Example 1, and X-ray diffraction and microstructure tests show that Example 2 contains intercalated or partially peeled montmorillonite sheets and nanocellulose distributed between the sheets, then it can be concluded that the present invention does not simply rely on increasing the resin thickness to achieve barrier properties, but rather improves the gas barrier performance of the composite material by synergistically constructing tortuous permeation channels through montmorillonite sheets and nanocellulose.

[0084] Comparative Example 2 did not contain plant wax, epoxidized soybean oil, or citric acid, and the bamboo powder was not subjected to any corresponding surface coating or interfacial reaction treatment. This comparative example was mainly used to evaluate the role of the moisture-proof and interfacial control system. If Example 2 exhibits lower water absorption and interfacial porosity compared to Comparative Example 2, and its tensile strength, elongation at break, and molded appearance are more stable, it indicates that plant wax can reduce the penetration of moisture into the composite material through the bamboo powder surface, and epoxidized soybean oil and citric acid can improve the interfacial bonding between bamboo powder, thermoplastic starch, and biodegradable resin, thereby reducing porosity, debonding, and cracking caused by differences in hydrophilicity and hydrophobicity.

[0085] Comparative Example 3 used the same formulation and dosage as Example 2, but without bamboo powder coating, nanocellulose pre-dispersion, and montmorillonite intercalation treatment, and underwent a one-time mixing at a higher temperature. This comparative example was mainly used to verify the effect of the low-temperature staged molding method of the present invention. If Example 2 has fewer coking particles, bubbles, and agglomeration regions, lower interfacial porosity, smaller torque fluctuations, and maintains better tensile and barrier properties compared to Comparative Example 3, it can be shown that there is a synergistic effect between raw material pretreatment, pre-dispersion preparation, staged feeding, low-temperature short-time mixing, and vacuum degassing, which can reduce the thermal degradation of bamboo powder and thermoplastic starch, and reduce the molecular chain breakage of polylactic acid caused by moisture and acidic substances.

[0086] When synthesizing the test results of each group, it is not advisable to use the maximum value of a single performance as the selection criterion alone. Instead, low-temperature molding stability, oxygen barrier properties, water vapor barrier properties, water absorption rate, interfacial porosity, and mechanical properties should be considered simultaneously. Examples 1 to 3 all meet the preset judgment criteria, and Example 2 shows a good overall balance among various properties, which demonstrates the feasibility of the formulation range defined by the present invention. Compared with the three comparative examples, Example 2 shows significant improvements in composite barrier structure, interfacial moisture-proof structure, and low-temperature molding stability, which further proves that the synergistic barrier of montmorillonite and nanocellulose, the interfacial regulation of plant wax, epoxidized soybean oil, and citric acid, and the staged low-temperature molding process are not simple superpositions of each other, but rather work together to affect the dispersion state, interfacial density, and penetration path structure of the composite material, thereby achieving low-temperature stable molding and high barrier performance of bamboo powder composite materials.

[0087] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A low-temperature molding method for a bamboo powder / biodegradable high-barrier composite material, characterized in that, The composite material comprises the following formulation: polylactic acid resin, PBAT resin, bamboo powder, thermoplastic starch, montmorillonite, nanocellulose, plant wax, epoxidized soybean oil, citric acid, talc, stearic acid, and antioxidants. The low-temperature molding method for this composite material includes the following steps: S1. Raw material drying and particle size classification; S2, bamboo powder surface activation and plant wax coating treatment; Preparation of S3, thermoplastic starch and nanocellulose predispersants; S4. Preparation of montmorillonite intercalation predispersant; S5, staged melt mixing and interfacial reaction; S6, exhaust extrusion, granulation and barrier structure orientation molding.

2. The low-temperature molding method for a bamboo powder / biodegradable high-barrier composite material according to claim 1, characterized in that, The composite material, by weight, comprises the following components: 45-70 parts polylactic acid resin, 15-35 parts PBAT resin, 10-30 parts bamboo powder, 5-18 parts thermoplastic starch, 2-8 parts montmorillonite, 1-6 parts nanocellulose, 1-5 parts plant wax, 1-5 parts epoxidized soybean oil, 0.3-2 parts citric acid, 1-6 parts talc, 0.3-1.5 parts stearic acid, and 0.1-0.8 parts antioxidant.

3. The low-temperature molding method for a bamboo powder / biodegradable high-barrier composite material according to claim 1, characterized in that, The raw material drying and particle size classification process includes: Polylactic acid resin and PBAT resin were dried at 55–70°C for 4–8 hours to reduce their moisture content to no more than 0.2%. Montmorillonite and talc were dried at 80–100°C for 2–5 hours to reduce their moisture content to no more than 1%. Bamboo powder is sieved into coarse-grained bamboo powder of 80-120 mesh and fine-grained bamboo powder of 160-200 mesh, and mixed in a mass ratio of 2:1 to 4:

1. Then it is dried at 80-100℃ until the moisture content is no more than 1.5% to obtain graded dried bamboo powder.

4. The low-temperature molding method for a bamboo powder / biodegradable high-barrier composite material according to claim 1, characterized in that, The bamboo powder surface activation and plant wax coating treatment includes: Based on the graded and dried bamboo powder obtained in step S1, it is added to an alkaline aqueous solution with a mass concentration of 1% to 3%, and the mass ratio of bamboo powder to alkaline aqueous solution is 1:8 to 1:

12. The mixture is stirred at 55 to 70°C for 30 to 60 minutes to remove some wax, ash and low molecular weight impurities from the surface of the bamboo powder. After processing, filter and wash with water until the washing liquid is neutral. Then, prepare a citric acid aqueous solution with a mass concentration of 0.5% to 2% using citric acid accounting for 30% to 60% of the total mass of citric acid in the formula. Immerse the washed bamboo powder in the solution for 20 to 40 minutes. The treated bamboo powder is dried at 80-100℃ until the moisture content is no more than 1.5%. Then, 40%-70% of the total mass of plant wax is heated to 75-90℃ to melt it and mixed with the dried bamboo powder for 5-15 minutes, so that the plant wax is attached to the surface of the bamboo powder in a discontinuous thin layer. After cooling and breaking it up, modified bamboo powder is obtained.

5. The low-temperature molding method for a bamboo powder / biodegradable high-barrier composite material according to claim 1, characterized in that, The preparation of the thermoplastic starch includes: Mix starch, glycerin and water in a mass ratio of 100:20-35:10-20, seal and let stand for 4-12 hours to allow the glycerin and water to evenly penetrate into the starch granules and form a mixture. The mixture is then added to a mixer or twin-screw extruder and plasticized at 110–140°C for 3–10 minutes. This process destroys the original crystalline structure of the starch granules and forms a continuous or semi-continuous plasticized phase. At the same time, free water is discharged through the exhaust port to obtain thermoplastic starch with a moisture content of no more than 3%.

6. The low-temperature molding method for a bamboo powder / biodegradable high-barrier composite material according to claim 1, characterized in that, The preparation of the nanocellulose predispersant includes: Nanocellulose and thermoplastic starch are premixed at a temperature of 105–135°C for 2–8 minutes to coat and isolate nanocellulose with a diameter of 20–80 nanometers and a length of 0.5–3 micrometers, thus obtaining nanocellulose predispersed material.

7. The low-temperature molding method for a bamboo powder / biodegradable high-barrier composite material according to claim 1, characterized in that, The preparation of the montmorillonite intercalation predispersant includes: Based on the obtained nanocellulose predispersed material, organomontmorillonite with an average particle size of 1-5 micrometers, an initial interlayer spacing of 1.8-3.0 nanometers and a moisture content of no more than 1% was premixed with epoxidized soybean oil, wherein the mass ratio of organomontmorillonite to epoxidized soybean oil used for premixing was 1:0.15-0.

40. The two materials are stirred at 300-800 rpm for 10-30 minutes at 60-90℃ to allow the epoxidized soybean oil to penetrate into the gaps between the montmorillonite layers and reduce the bonding force between adjacent layers, thus obtaining the montmorillonite intercalation pre-dispersion material.

8. The low-temperature molding method for a bamboo powder / biodegradable high-barrier composite material according to claim 1, characterized in that, The staged melt mixing includes: Based on the obtained modified bamboo powder, nanocellulose predispersed material and montmorillonite intercalated predispersed material, the dried polylactic acid resin and PBAT resin were first added to the front section of a twin-screw extruder and melt-mixed at 150-165°C to disperse the PBAT resin in the continuous phase of polylactic acid resin. Subsequently, modified bamboo powder, nanocellulose predispersant and montmorillonite intercalated predispersant are added sequentially from the middle section of the extruder, and talc is added to disperse and shear the solid components in the resin matrix. After the components are initially dispersed, the remaining epoxidized soybean oil, citric acid and vegetable wax are added, along with stearic acid and antioxidants. The mixture is then further mixed at 160–175°C for 1–4 minutes to form a melt blend.

9. The low-temperature molding method for a bamboo powder / biodegradable high-barrier composite material according to claim 1, characterized in that, The exhaust extrusion and granulation include: Based on the melt blend formed in step S5, vacuum degassing is performed in the rear section of the twin-screw extruder, with the vacuum degree controlled at -0.06 to -0.095 MPa, to remove moisture, air and low-molecular-weight volatiles; The molten blend was then extruded through a die, cooled, and pelletized to obtain bamboo powder / biodegradable high-barrier composite material particles.

10. The low-temperature molding method for a bamboo powder / biodegradable high-barrier composite material according to claim 9, characterized in that, The screw speed of the twin-screw extruder is 120-300 rpm, and the extrusion temperature is controlled sequentially from the feed end to the discharge end at 140-155℃, 150-165℃, 160-175℃, 165-175℃ and 155-170℃. After drying the obtained granules again at 55–70°C for 4–8 hours, they are formed by blown film, cast film, extrusion or hot pressing.